Pengaruh Perceived Value Terhadap Kepuasan Implementasi Program MBKM - Feni Marnilin; Isbandriyati Mutmainah; Iis Anisa Yulia; Ahmad Zaid Mahfudi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Perceived value and student satisfaction are important aspects in higher education. The Ministry of Education, Culture, Research and Technology plans the Merdeka Belajar Kampus Merdeka (MBKM) program to be able to equip students to learn from various disciplines that are relevant to their interests and needs to enter the world of work. The Faculty of Economics and Business, University of Nusa Bangsa has organized the MBKM program with two programs, namely Student Exchange and KKNT. This study aims to determine the level of success of the MBKM program that has been carried out by analyzing the perceived value of the satisfaction of the MBKM program implementation. The analytical method used is multiple linear regression analysis with the dependent variable is implementation satisfaction, and the independent variable is perceived functional value, perceived emotional value, perceived social value. The results showed that partially perceived functional value and perceived social value had an effect, while simultaneously all independent variables had an effect on dependent satisfaction. Keywords: perceived value, satisfaction, MBKM